Assessment of Stereoscopic Multi-resolution Images for a Virtual Reality System - Ogawa, Masahiko; Shidoji, Kazunori; Matsuki, Yuji (International Journal of Virtual Reality, 2010)
A camera and monitor system that projects actual real-world images has yet to be developed due to the technical limitation that the existing cameras cannot simultaneously acquire high-resolution and wide-angle images. In this research, we try to resolve this issue by superimposing images; a method which is effective because the entire wide-angle image does not necessarily need to be of high resolution because of perceptual characteristics of the human visual system. First, we examined the minimum resolution required for the field of view, which indicated that a triple-resolution image where positions more than 20 and 40 deg from the center of the visual field were decreased to 25% and approximately 11% of the resolution of the gaze point, respectively, was perceived as similar to a completely high-resolution image. Next, we investigated whether the participants could distinguish between the original completely high-resolution image and processed images, which included triple-resolution, dual-resolution, and low-resolution images. Our results suggested that the participants could not differentiate between the triple-resolution image and the original image. Finally, we developed a stereoscopic camera system based on our results